Reconstruction of Pacta Sunt Servanda in Fiduciary Execution after Constitutional Court Decision No. 18/2019 - A. Abdul, Topan; lahaling, Hijrah; Rusmulyadi (Cattleya Darmaya Fortuna, 2025)
The development of consumer financing agreements secured by fiduciary guarantees in Indonesia has long relied on the principle of pacta sunt servanda as the primary legal foundation for contractual enforcement. Traditionally, this principle was applied in a rigid and formalistic manner, allowing creditors to unilaterally determine default and execute fiduciary collateral based solely on contractual provisions and fiduciary certificates. Such practices often resulted in an imbalance of legal positions between creditors and debtors, particularly due to the dominance of standard-form contracts. The Constitutional Court Decision Number 18/PUU-XVII/2019 marked a significant shift by asserting that default cannot be determined unilaterally and that fiduciary execution without debtor consent or judicial determination violates constitutional protections. This research aims to analyze the application of the pacta sunt servanda principle in consumer financing agreements before and after the Constitutional Court decision and to reconstruct the principle in order to achieve a fair, balanced, and constitutionally compliant model of fiduciary execution. Employing a normative juridical method, this study examines statutory regulations, legal doctrines, and relevant court decisions to identify changes in legal interpretation and enforcement practices. The findings indicate that the Constitutional Court decision has transformed pacta sunt servanda from an absolute principle into a conditional one that must be integrated with principles of justice, proportionality, good faith, and constitutional rights protection. The study concludes that the reconstruction of pacta sunt servanda is essential to harmonize contractual certainty with substantive justice, ensuring that fiduciary execution mechanisms in Indonesia respect both private autonomy and constitutional guarantees.